All-solid secondary battery

JP2023101001A5Pending Publication Date: 2025-04-01SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023080973
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-11-11
Filing Date
2023-05-16
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Lithium-ion batteries are prone to overheating and fire due to the use of flammable organic solvents, and all-solid-state batteries with insufficient contact between layers lead to high resistance and potential short circuits, hindering excellent battery characteristics.

Method used

An all-solid secondary battery design with a positive electrode layer, negative electrode layer, and solid electrolyte layer, incorporating an inert member to maintain contact and prevent cracking during pressurization, thereby preventing short circuits and improving cycle characteristics.

Benefits of technology

The design effectively suppresses cracking in the solid electrolyte layer, preventing short circuits and enhancing the cycle characteristics of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide an all-solid secondary battery.SOLUTION: Provided is an all-solid secondary battery comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer. The positive electrode layer includes a positive electrode collector, a positive electrode active material layer disposed on the positive electrode collector, and an inert member disposed on one side face of the positive electrode active material layer. The negative electrode layer includes a negative electrode collector, and a first negative electrode active material layer disposed on the negative electrode collector.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to an all-solid-state secondary battery. [Background technology]

[0002] Recently, industrial demands have led to a surge in the development of batteries with high energy density and superior safety. It is being done. For example, lithium-ion batteries are used not only in the information-related equipment field and the communication equipment field. However, it is not only not used in the automotive sector, but is also put into practical use in the automotive sector. In the automotive sector, it is related to life. Therefore, safety is given particular importance. Lithium-ion batteries currently on the market contain flammable organic solvents and utilize an electrolyte solution. Therefore, if a short circuit occurs, there is a possibility of overheating and fire. To counter these, electrolysis All-solid-state batteries that utilize a solid electrolyte instead of a liquid electrolyte have been proposed. Because this all-solid-state battery does not use flammable organic solvents, even if a short circuit occurs, it will not cause a fire or The possibility of explosions can be greatly reduced. Therefore, such all-solid-state batteries Compared to lithium-ion batteries that use electrolytes, this significantly improves safety. [Overview of the Initiative] [Problems that the invention aims to solve]

[0003] One aspect of the present invention is to provide an all-solid-state secondary battery with a novel structure. [Means for solving the problem]

[0004] In one example, a positive electrode layer, a negative electrode layer, and a solid disposed between the positive electrode layer and the negative electrode layer. The positive electrode layer comprises a body electrolyte layer, and the positive electrode layer is disposed on the positive electrode current collector. A positive electrode active material layer, and an insulator disposed on one side surface (for example, one or more sides) of the positive electrode active material layer. The negative electrode layer includes an inactive member, and the negative electrode current collector and A solid-state secondary battery is provided, which includes a first negative electrode active material layer disposed on the negative electrode current collector. [Effects of the Invention]

[0005] To provide an all-solid-state secondary battery with excellent cycle characteristics and short-circuit prevention through one side. This is possible. [Brief explanation of the drawing]

[0006] [Figure 1] This is a cross-sectional view of an all-solid-state secondary battery, illustrating one exemplary example. [Figure 2] This is a cross-sectional view of an all-solid-state secondary battery, illustrating one exemplary example. [Figure 3] This is a schematic diagram of the cathode layer of an all-solid-state secondary battery, illustrating one exemplary example. [Figure 4] This is a schematic diagram partially showing the internal structure of an all-solid-state secondary battery, representing one exemplary example. [Modes for carrying out the invention]

[0007] In all-solid-state secondary batteries, since the electrolyte is solid, there is a gap between the positive electrode layer and the solid electrolyte layer, and between the positive electrode and the negative electrode. If contact between the layer and the solid electrolyte layer is not sufficiently maintained, the resistance within the battery will be high. This makes it difficult for the battery to exhibit superior performance characteristics.

[0008] In order to improve contact between the negative electrode layer and the solid electrolyte, in the manufacturing process of all-solid-state secondary batteries , undergoes a pressurization process. During this pressurization process, the laminate including the positive electrode layer, the negative electrode layer and the solid electrolyte layer In this case, a pressure difference occurs in the parts that are not laminated, and due to such a pressure difference, the solid Microscopic defects can occur in the electrolyte layer. During the charge-discharge process of all-solid-state secondary batteries, Such defects cause cracks to form and grow within the solid electrolyte layer. Through such cracks, As the thium grows, a short circuit may occur between the positive and negative electrode layers. The all-solid-state secondary battery with a single side surface has a novel structure that prevents short circuits during charging and discharging. This can stop the process and improve cycle characteristics.

[0009] The present inventive concept described below t) can be subjected to various transformations and can have various embodiments, but particularly A typical implementation is illustrated in the drawings and explained in detail. However, this creative idea may not be applicable to specific situations. This does not limit the form of implementation to all transformations included within the technical scope of this innovative idea. It must be understood that this includes equivalents or substitutes.

[0010] The terms used below are used solely to describe specific examples. This is not intended to limit the scope of this original idea. The singular expression, depending on the context, clearly has a different meaning. Unless otherwise specified, it includes multiple expressions. In the following, the usage of "includes" or "possesses" The words are features, numbers, stages, operations, components, parts, ingredients, materials, and also as described in the specification. This indicates that such combinations exist, and one or more other The presence of features, letters, stages, actions, components, parts, ingredients, materials, or combinations thereof. It must be understood that this does not preemptively rule out the possibility of additions. The " / " used below can be interpreted as either "and" or "or" depending on the context. Shut up.

[0011] In drawings, thicknesses are sometimes enlarged or reduced to clearly represent various layers and areas. They are shown in a smaller size or similar manner. Throughout the specification, similar parts are given the same reference numerals. Throughout the specification, parts such as layers, films, regions, and plates are referred to as "on top of" or "on the upper part" of other parts. When we consider that it is located in a certain position, it is not only when it is directly above another part, but also when there is another part in between. This includes cases where there are parts. Throughout the specification, terms such as "1" and "2" refer to various constituent elements. While it can be used to describe elements, the constituent elements are not limited by the terminology. The terminology used herein is solely for the purpose of distinguishing one component from another. In the drawings, components having substantially the same functional configuration are referred to by the same reference numeral. This eliminates redundant explanations.

[0012] The following provides a more detailed explanation of all-solid-state secondary batteries using illustrative examples. . [All-solid-state secondary battery] An example of an all-solid-state secondary battery consists of a positive electrode layer, a negative electrode layer, and an arrangement between the positive and negative electrode layers. A solid electrolyte layer is provided, and the positive electrode layer is disposed on the positive electrode current collector. A positive electrode active material layer, and an inactive material disposed on one side (e.g., one or more sides) of the positive electrode active material layer. The negative electrode layer includes an inactive member, and the negative electrode current collector and negative electrode current collector It includes a first negative electrode active material layer disposed on the electrostatic body. One side surface (for example, one or more) of the positive electrode active material layer. By including an inert member placed on the side surface, when the all-solid-state secondary battery is pressurized, the solid-state battery Cracks in the dissolved solid layer are suppressed. Therefore, during charging and discharging of an all-solid-state secondary battery, cracks in the solid electrolyte layer are suppressed. This suppresses short circuits in all-solid-state secondary batteries. This can improve the cyclical characteristics of the pond.

[0013] Referring to Figures 1 to 4, the all-solid-state secondary battery 1 has a positive electrode layer 10 and negative electrode layers 20, 20a ,20b, and the solid electrolyte disposed between the positive electrode layer 10 and the negative electrode layers 20,20a,20b. The positive electrode layer 10 includes layers 30, 30a, and 30b, and the positive electrode layer 10 is on the positive electrode current collector 11, and on the positive electrode current collector The positive electrode active material layers 12, 12a, 12b are arranged in a positive electrode active material layer, and one side surface of the positive electrode active material layer (for example, Includes an inactive member 40 arranged on one or more sides. The negative electrode layers 20, 20a, 20b, the negative electrode current collectors 21, 21a, 21b, and the negative electrode current collector It includes first negative electrode active material layers 22, 22a, and 22b positioned on top.

[0014] [Positive electrode layer] [Positive electrode layer: Inert material] The positive electrode layer 10 consists of a positive electrode current collector 11 and a positive electrode active material layer 12, 1 disposed on the positive electrode current collector. It includes 2a, 12b, and an inert member 40 disposed on one side surface of the positive electrode active material layer.

[0015] The inert member 40 is an electrochemically active substance, for example, an electrode active material (electr The component does not contain an electrode active material. The electrode active material is a ri It is a substance that absorbs / releases thium. The inert member 40 is a substance other than the electrode active material. This is a component made of a material used in the relevant technical field.

[0016] The inert member 40 surrounds the sides of the positive electrode active material layers 12, 12a, and 12b, and the solid electrolyte The inert member 40 can come into contact with layers 30, 30a, and 30b. It surrounds the sides of 12a and 12b and is in contact with the solid electrolyte layers 30, 30a, and 30b. As a result, the solid electrolyte layers 30, 30a, 3 do not come into contact with the positive electrode active material layers 12, 12a, 12b. In 0b, a solid electrolyte layer 30 is generated by the pressure difference during the pressurization process. This effectively suppresses cracks in 30a and 30b.

[0017] The inert member 40 extends to the end portions of the solid electrolyte layers 30, 30a, and 30b. By extending the active member 40 to the end portions of the solid electrolyte layers 30, 30a, and 30b, This makes it possible to suppress cracks that occur at the ends of the solid electrolyte layers 30, 30a, and 30b. The ends of the solid electrolyte layers 30, 30a, and 30b are on the sides of the solid electrolyte layers 30, 30a, and 30b. This is the outermost part that is in contact with the surface. That is, the inert member 40 is the solid electrolyte layer 30, 30a It extends to the outermost part that is in contact with the side of 30b.

[0018] The area S1 of the positive electrode active material layers 12, 12a, and 12b is equal to the area of ​​the positive electrode active material layers 12, 12a, and 12b The area S2 of the solid electrolyte layers 30, 30a, and 30b that come into contact with the inert member 4 is smaller than that of the inert member 4. 0 is arranged surrounding the sides of the positive electrode active material layers 12, 12a, and 12b, and positive electrode active material layer 1 Area difference between 2,12a,12b and solid electrolyte layers 30,30a,30b The ror can be corrected. The area S3 of the inert member 40 is the positive electrode active material layer 12,1 Correct the difference between the area S1 of 2a and 12b and the area S2 of the solid electrolyte layers 30, 30a, and 30b. As a result, solid electrolyte layers 30, 30a, 30 are generated by the pressure difference during the pressurization process. Cracks in b can be effectively suppressed. For example, in the positive electrode active material layers 12, 12a, and 12b. The area S1 is less than 100% and 99% or less of the area S2 of the solid electrolyte layers 30, 30a, and 30b. It can also be below 98%, below 97%, below 96%, below 95%, or below 93%. For example The area S1 of the positive electrode active material layers 12, 12a, 12b is equal to the area of ​​the solid electrolyte layers 30, 30a, 30b Area S2 is less than 50% to 100%, 50% to 99%, 55% to 98%, 6 0% to 97%, 70% to 96%, 80% to 95%, or 85% to 95% Also, the area S1 of the positive electrode active material layers 12, 12a, 12b is equal to the area of ​​the solid electrolyte layers 30, 30a If the area S2 of 30b is the same as or larger than that of the positive electrode active material layer, 12,12a,12b and the negative electrode active material layers 22,22a,22b are in physical contact, causing a short circuit. The possibility of this occurring, or of a short circuit occurring due to lithium overcharging, increases.

[0019] The area S3 of the inert member 40 is 50% of the area S1 of the positive electrode active material layers 12, 12a, and 12b. The following are also true: 40% or less, 30% or less, 20% or less, or 10% or less. For example, inert. The area S3 of component 40 is 1% to 50% of the area S1 of the positive electrode active material layers 12, 12a, and 12b. %, 5% to 40%, 5% to 30%, 5% to 20%, or 5% to 15% Also, the area S3 of the inert member 40 and the area S1 of the positive electrode active material layers 12, 12a, 12b The sum of these two values ​​is also equal to the area S2 of the solid electrolyte layers 30, 30a, and 30b.

[0020] The inert member 40 is placed between the opposing positive electrode current collectors 11 and the solid electrolyte layer 30. They are either placed there, or they are also placed between two opposing solid electrolyte layers 30a and 30b. The inert member 40 is located between the opposing positive electrode current collectors 11 and the solid electrolyte layer 30. A filler that fills the space between, or between, two solid electrolyte layers 30a and 30b that are facing each other. It can perform the role of a filler.

[0021] The area S1 of the positive electrode active material layers 12, 12a, 12b is equal to the area of ​​the negative electrode current collectors 21, 21a, 21b. It is small even compared to area S4. For example, the area S1 of the positive electrode active material layers 12, 12a, and 12b is Area S4 of negative electrode current collectors 21, 21a, 21b less than 100%, 99% or less, 98% or less, It can also be 97% or less, 96% or less, 85% or less, or 93% or less. For example, the positive electrode active material layer. The area S1 of 12, 12a, 12b is 50 of the area S4 of the negative electrode current collectors 21, 21a, 21b. % or less than 100%, 50% or 99%, 55% or 98%, 60% or 97% It could be 70% or 96%, 80% or 95%, or 85% or 95%.

[0022] The area S4 of the negative electrode current collectors 21, 21a, 21b is equal to the area S5 of the positive electrode current collector 11 and / or They also have the same form. For example, the area S4 of the negative electrode current collectors 21, 21a, and 21b is the same as that of the positive electrode current collectors. Area S5 of the electric body 11 in the range of 100±5%, 100±3%, 100±2%, and 100±1 It is also a % range or a 100±0.5% range. The area S5 of the positive electrode current collector 11 is the solid electrolyte The areas S2 and / or shapes of layers 30, 30a, and 30b are also identical. For example, positive electrode current collection. The area S5 of body 11 is within 100±5% of the area S2 of the solid electrolyte layers 30, 30a, and 30b. , 100±3%, 100±2%, 100±1%, or 100±0.5% range Yes. In this specification, "identical" area and / or form means area and / or form Unless intentionally made different, all having "substantially identical" area and / or form. This includes the case of

[0023] The inert member 40 is selected from lithium-ion insulators and lithium-ion conductors. It may contain one or more of the above. The inert member 40 is also an electronic insulator. Alternatively, it may be an inert Component 40 does not have to be an electronic conductor.

[0024] The inert member 40 is an organic material, an inorganic material, or an inorganic composite material. The organic material is For example, it is also a polymer. The inorganic material is, for example, a ceramic such as a metal oxide. There are also inorganic composite materials. The inorganic composite material is also a composite of polymer and metal oxide. Inert member 40 Examples include insulating polymers, ion-conducting polymers, insulating inorganic materials, oxide-based solid electrolytes, It may also contain one or more selected from sulfide-based solid electrolytes. The inert member 40 is, for example, For example, even olefin polymers such as polypropylene (PP) and polyethylene (PE) be.

[0025] The density of the inert member 40 is, for example, the density of the positive electrode active material layer 12, 12a, 12b. 10% to 200%, 10% to 150%, 10% to 140% of the density of the active material, The density of the inert member 40 is 10% to 130%, or 10% to 120%. For example, the density of the positive electrode active material contained in the positive electrode active material layers 12, 12a, and 12b is 90 to It is also 110%. The density of the inert material 40 is, for example, that of the positive electrode active material layers 12, 12a, 12 It is also substantially the same as the density of the positive electrode active material contained in b.

[0026] The inert member 40 is, for example, a gasket. When used, the solid electrolyte layer 30,30 generated by the pressure difference during the pressurization process Cracks in a and 30b can be effectively suppressed.

[0027] [Cathode layer: Cathode active material] The positive electrode active material layers 12, 12a, and 12b include, for example, a positive electrode active material and a solid electrolyte. The solid electrolyte contained in the polar layer 10 is the solid electrolyte contained in the solid electrolyte layers 30, 30a, and 30b. It may be similar to or different from the solution. Details regarding the solid electrolyte are as follows: Refer to electrolyte layers 30, 30a, and 30b.

[0028] The positive electrode active material reversibly absorbs and desorbs lithium ions. The positive electrode active material is capable of rb. The positive electrode active material is, for example, lithium cobalt Oxide (LCO), lithium nickel oxide (lithium nickel oxid e) Lithium nickel cobalt oxide (Oxide), Lithium nickel cobalt aluminum oxide (NCA), Lithium Cobalt manganese oxide (NCM), lithium manganese oxide (lithium manganate), lithium iron phosphate (lithium iron phos Lithium transition metal oxides such as phate; nickel sulfide; copper sulfide, lithium sulfide, Iron oxide; or vanadium oxide, etc., but not always However, it is not limited to those, and in the field of the art, it is used as a positive electrode active material. If they are such that, then all are possible. The positive electrode active material can also be used individually. It is also a mixture of two or more things.

[0029] The positive electrode active material is, for example, the lithium transition metal oxide is, for example, Li a A 1-b B ' b D2 (where 0.90 ≤ a ≤ 1 and 0 ≤ b ≤ 0.5 in the above chemical formula), Li a E 1- b B’ b O 2-c D c (In the above chemical formula, 0.90 ≤ a ≤ 1, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0 .05), LiE 2-b B’ b O 4-c D c (In the above chemical formula, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05), Li a Ni 1-b-c Co b B’ c D α (In the above chemical formula, 0. 90 ≤ a ≤ 1, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α ≤ 2), Li a Ni1 -b-c Co b B’ c O 2-α F’ α (In the above chemical formula, 0.90 ≤ a ≤ 1, 0 ≤ b ≤ 0. 5, 0 ≤ c ≤ 0.05, 0 < α < 2), Li a Ni 1-b-c Co b B’ c O 2- α F’2(In the above chemical formula, 0.90 ≤ a ≤ 1, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α < 2), Li a Ni 1-b-c Mn b B’ c D α (In the above chemical formula, 0.90 ≤ a ≤ 1, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α ≤ 2), Li a Ni 1-b-c Mn b B’ c O 2-α F’ α (In the above chemical formula, 0.90 ≤ a ≤ 1, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α < 2), Li a Ni 1-b-c Mnb B' c O 2-α F'2 (In the above chemical formula, 0.90 ≤ a ≤ 1, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α < 2) (Yes), Li a Ni b E c G d O2 (In the above chemical formula, 0.90 ≤ a ≤ 1, 0 ≤ b ≤ 0.9) (where 0≦c≦0.5 and 0.001≦d≦0.1), Li a Ni b Co c Mn d GeO 2 (In the above chemical formula, 0.90 ≤ a ≤ 1, 0 ≤ b ≤ 0.9, 0 ≤ c ≤ 0.5, 0 ≤ d ≤ 0. 5, 0.001 ≤ e ≤ 0.1), Li a NiG b O2 (in the above chemical formula, 0.90 ≤ (where a ≤ 1 and 0.001 ≤ b ≤ 0.1), Li a CoG b O2 (in the above chemical formula, 0.9 (0 ≤ a ≤ 1, 0.001 ≤ b ≤ 0.1), Li a MnG b O2 (in the above chemical formula, 0 (0.90≦a≦1, 0.001≦b≦0.1), Li a Mn2G b O4 (the above chemical formula) (Therefore, 0.90≦a≦1, 0.001≦b≦0.1), QO2, QS2, LiQS2 , V2O5, LiV2O5, LiI'O2, LiNiVO4, Li (3-f) J2 (PO) 4) 3 (0 ≤ f ≤ 2), Li (3-f) Fe2(PO4)3(0≦f≦2), LiFeP It is a compound that can be represented by one of the chemical formulas for O4. In this example, A is Ni, Co, Mn, or a combination thereof, and B' is Al, N i, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements, or combinations thereof And D is O, F, S, P, or a combination thereof, and E is Co, Mn, Or a combination thereof, and F' is F, S, P, or a combination thereof. G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or combinations thereof. It is a combination, Q is Ti, Mo, Mn, or a combination thereof, and I' is C r, V, Fe, Sc, Y, or a combination thereof, and J is V, Cr, Mn, C It is o, Ni, Cu, or a combination thereof. A coating is applied to the surface of such a compound. Compounds with a coating layer can also be used, and the aforementioned compounds with a coating layer can be used. It is also possible to use a mixture with the compound. The coating layer is, for example, an oxide of the coating element, a hydroxide of the coating element , coating element oxyhydroxyl, coating element oxycarbonate, It contains a coating element compound of hydroxycarbonate, which is a coating element. Compounds forming such coating layers are amorphous or crystalline. The coating elements that can occur include Mg, Al, Co, K, Na, Ca, Si, Ti, and V. The coating layer is made of Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The method for forming the coating is selected within a range that does not adversely affect the physical properties of the positive electrode active material. Coating methods include, for example, spray coating and immersion coating. The method of application is well known to those skilled in the art, therefore, a detailed explanation is omitted. do.

[0030] The positive electrode active material is, for example, a layered rock salt type (la) in the lithium transition metal oxide mentioned above. Lithium salts of transition metal oxides having a layered rock salt type structure are included. The "layered rock salt type structure" is, for example, in the <111> direction of the cubic rock salt type (cubic rock salt type) structure, an oxygen atom layer and a metal atom layer are regularly arranged alternately, such that each atomic layer forms a two-dimensional plane. The "cubic rock salt type structure" is a sodium chloride type (NaCl type) structure which is a kind of crystal structure, specifically, a face-centered cubic lattice (fcc: face centered cubic lattice) formed by cations and anions respectively is arranged so that they are offset by about 1 / 2 of the ridge of the unit lattice (unit lattice). A lithium transition metal oxide having such a layered rock salt type structure is, for example, LiNi Co Al x Co y Al z O2 (NCA) or LiNi x Co y Mn z O2 (NCM) (0 < x < 1, 0 < y < 1, 0 < z < 1, x + y + z = 1) such as a ternary lithium transition metal oxide When the positive electrode active material includes a ternary lithium transition metal oxide having a layered rock salt type structure the energy density and thermal stability of the all-solid-state secondary battery 1 are further improved.

[0031] The positive electrode active material is also covered with a coating layer as described above. The coating layer may be any one if it is known as a coating layer for the positive electrode active material of an all-solid-state secondary battery The coating layer is, for example, Li2O-ZrO2 (LZO) or the like.

[0032] The positive electrode active material is, for example, a ternary lithium transition metal oxide such as NCA or NCM. Therefore, when nickel (Ni) is included, it increases the capacity density of the all-solid-state secondary battery 1, and the rechargeable This allows for the reduction of metal leaching from the positive electrode active material. As a result, the charge state of the all-solid-state secondary battery 1 This can improve the cycle characteristics in the context of the system.

[0033] The shape of the positive electrode active material is particulate, such as a perfect sphere or an ellipsoid. The particle size is not specifically limited and is applicable to the positive electrode active material of conventional all-solid-state secondary batteries. It is within the limits of what is possible. The content of the positive electrode active material in the positive electrode layer 10 is not particularly limited, and This is applicable to the positive electrode layer of future all-solid-state secondary batteries.

[0034] [Positive electrode layer: solid electrolyte] The positive electrode active material layers 12, 12a, and 12b may, for example, contain a solid electrolyte. The solid electrolyte contained in 0 is the solid electrolyte contained in the solid electrolyte layers 30, 30a, and 30b. They may be the same or different. For detailed information regarding the solid electrolyte, see Solid Electrolyte Refer to layers 30, 30a, and 30b.

[0035] The solid electrolyte contained in the positive electrode active material layers 12, 12a, and 12b is the solid electrolyte layer 30, 30 The average particle size of D50 is smaller compared to the solid electrolyte contained in a and 30b. For example, The average D50 particle size of the solid electrolyte contained in the extremely active material layers 12, 12a, and 12b is: The average D50 particle size of the solid electrolyte contained in layers 30, 30a, and 30b is 90% or less, and 80% or less. Below 70%, below 60%, below 50%, below 40%, below 30%, or below 20% There are also others.

[0036] [Positive electrode layer: Binder] The positive electrode active material layers 12, 12a, and 12b may contain a binder. The binder may be, for example, Styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinyl fluoride Examples include redene and polyethylene.

[0037] [Positive electrode layer: conductive agent] The positive electrode active material layers 12, 12a, and 12b may contain a conductive agent. The conductive agent may be, for example, Graphite, carbon black, acetylene black, Ketjen black, Examples include carbon fiber and metal powder.

[0038] [Positive electrode layer: Other additives] The positive electrode active material layers 12, 12a, and 12b consist of the aforementioned positive electrode active material, solid electrolyte, binder, and conductive material. In addition to electrolytic agents, other additives such as fillers, coating agents, dispersants, and ion conductivity enhancers are also used. Further additives may be included.

[0039] Fillers, coating agents, dispersants, and ions contained in the positive electrode active material layers 12, 12a, and 12b As conductive additives, etc., generally known materials used in electrodes of all-solid-state secondary batteries. You can use it.

[0040] [Positive electrode layer: Positive electrode current collector] The positive electrode current collector 11 is made of, for example, indium (In), copper (Cu), or magnesium (Mg). Stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (N) i) Zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) or use a plate or foil made of such an alloy. The positive electrode current collector 11 is optional.

[0041] [Solid electrolyte layer] [Solid electrolyte layer: solid electrolyte] Referring to Figures 1 through 4, the solid electrolyte layers 30, 30a, and 30b are connected to the positive electrode layer 10 and the negative electrode layer. It contains a solid electrolyte placed between the polar layers 20, 20a, and 20b.

[0042] The solid electrolyte is, for example, a sulfide-based solid electrolyte. Li2S-P2S5, Li2S-P2S5-LiX (where X is a halogen element), L i2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-Si S2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS 2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5 -LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (m and n are positive numbers) (where Z is one of Ge, Zn, or Ga), Li2S-GeS2, Li2S-S iS2-Li3PO4, Li2S-SiS2-Li p MO q (p and q are positive numbers, M (It is one of P, Si, Ge, B, Al, GaIn), Li 7-x PS 6-x C l x (0≦x≦2), Li 7-x PS 6-x Br x (0≦x≦2) and Li 7-x PS6 -x I x It is one or more selected from (0≦x≦2). The sulfide-based solid electrolyte is For example, starting materials such as Li2S and P2S5 can be processed using methods such as melt-quenching or mechanical milling (mec It is produced by processing methods such as hanical milling. After the treatment, heat treatment can be performed. The solid electrolyte can be amorphous, crystalline, or a mixture of them. Also, the solid electrolyte includes, for example, at least sulfur (S), phosphorus (P), and lithium (Li) as constituent elements among the aforementioned sulfide-based solid electrolyte materials. For example, the solid electrolyte can be a material containing Li2S-P2S5. When using a sulfide-based solid electrolyte material containing Li2S-P2S5 to form the solid electrolyte, the mixing molar ratio of Li2S and P2S5 is, for example, in the range of Li2S:P 2S5 = 50:50 to 90:10.

[0043] The sulfide-based solid electrolyte may include, for example, an argyrodite type solid electrolyte represented by the following chemical formula 1: (Chemical formula 1) Li + 12-n-x A n+ X 2- 6-x Y - x

[0044] In the above chemical formula 1, A is P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti , V, Nb or Ta, X is S, Se or Te, Y is Cl, Br, I , F, CN, OCN, SCN or N3, 1 ≤ n ≤ 5, 0 ≤ x ≤ 2. The sulfide-based solid electrolyte includes, for example, Li 7-x PS 6-x Cl x (0 ≤ x ≤ 2), Li 7-x P S 6-x Br x (0 ≤ x ≤ 2) and Li 7-x PS 6-x I x (0 ≤ x ≤ 2) among them. ​​​It is also an argyrodite-type compound containing one or more selected elements. For example, selected from Li6PS5Cl, Li6PS5Br, and Li6PS5I. It is also an argyrodite-type compound containing one or more of the specified compounds.

[0045] The density of the argyrodite-type solid electrolyte is 1.5 to 2.0 g / cc. The argyrodite-type solid electrolyte has a density of 1.5 g / cc or more. The internal resistance of all-solid-state secondary batteries is reduced, and the penetration of the solid electrolyte layer by Li (penetration) is reduced. It can effectively suppress (tion).

[0046] [Solid electrolyte layer: binder] The solid electrolyte layers 30, 30a, and 30b may, for example, contain a binder. The binder contained in layers 30, 30a, and 30b is, for example, styrene-butadiene rubber (SB R) also includes polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc. However, it is not limited to those, and in the field of the relevant technology, it is used as a binder. If so, then all are possible. The binders of the solid electrolyte layers 30, 30a, and 30b D is the same as the binder contained in the positive electrode active material layers 12, 12a, 12b and the negative electrode active material layer 22. They may be the same, or they may be different.

[0047] [Negative electrode layer] [Negative electrode layer: negative electrode active material] The first negative electrode active material layers 22, 22a, and 22b include, for example, a negative electrode active material and a binder.

[0048] The negative electrode active material contained in the first negative electrode active material layers 22, 22a, and 22b is, for example, in particle form. It has. The average particle size of the negative electrode active material having the particle form is, for example, 4 μm or less, 3 μm or less. The particle size is 2 μm or less, 1 μm or less, or 900 nm or less. The average particle size is, for example, 10 nm to 4 μm or less, 10 nm to 3 μm or less, 10 nm m or less than 2 μm, 10 nm or less than 1 μm, or 10 nm or less than 900 nm Therefore, the negative electrode active material has an average particle size within such a range, during charging and discharging, lithium The reversible absorbing and / or desorbing of um It also becomes easier. The average particle size of the negative electrode active material can be determined, for example, by using a laser particle size analyzer. This is the median diameter (D50) measured using this method.

[0049] The negative electrode active material contained in the first negative electrode active material layers 22, 22a, and 22b is, for example, a carbon-based negative electrode. The active material comprises one or more selected from among a metallic anode active material or a quasi-metallic anode active material. .

[0050] The carbon-based negative electrode active material is, in particular, amorphous carbon. The amorphous carbon is, for example, carbon black (CB) and acetylene black (AB). Other examples include Furnace Black (FB), Ketjen Black (KB), and graphene. However, it is not necessarily limited to those, and in the field of the art, amorphous carbon is used for division If they are similar, then any of them are possible. The amorphous carbon does not possess crystalline properties. Alternatively, it is carbon with very low crystallinity and is classified as crystalline carbon or graphite-based carbon.

[0051] The metal anode active material or the quasi-metallic anode active material is gold (Au), platinum (Pt), palladium Pd (Particleboard), Silicon (Si), Silver (Ag), Aluminum (Al), Bismas (Bi) It includes one or more elements selected from the group consisting of tin (Sn) and zinc (Zn), but not necessarily all of the above. Not limited to these, but in the art, lithium and alloys or compounds If it is to be used as a metallic anode active material or quasi-metallic anode active material to be formed, Misalignment is also possible. For example, nickel (Ni) does not form an alloy with lithium, so gold It is not a negative electrode active material.

[0052] The first negative electrode active material layers 22, 22a, and 22b are one type of negative electrode active material among such negative electrode active materials. It contains a substance or a mixture of several different negative electrode active materials. For example, the first negative The highly active material layers 22, 22a, and 22b contain only amorphous carbon, or gold (Au), white Gold (Pt), Palladium (Pd), Silicon (Si), Silver (Ag), Aluminum (Al One or more elements selected from the group consisting of ), vizmas (Bi), tin (Sn), and zinc (Zn). This includes. As an alternative, the first negative electrode active material layers 22, 22a, and 22b consist of amorphous carbon and gold (A u), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum Selected from the group consisting of aluminum (Al), bizma (Bi), tin (Sn), and zinc (Zn). It contains a mixture of one or more of the following: amorphous carbon, gold (Au), platinum (Pt), and palladium (P d) Silicon (Si), Silver (Ag), Aluminum (Al), Vizmas (Bi), Tin The mixing ratio of a mixture with one or more elements selected from the group consisting of (Sn) and zinc (Zn) is: In terms of quantity ratio, for example, 10:1 or 1:2, 5:1 or 1:1, or 4:1 or While it can be 2:1, it is not necessarily limited to that range, and all required solid The characteristics of the secondary battery 1 are selected. The negative electrode active material has such a composition. This further improves the cycle characteristics of the all-solid-state secondary battery 1.

[0053] The negative electrode active material contained in the first negative electrode active material layers 22, 22a, and 22b is, for example, amorphous carbon. It comprises a mixture of first particles made of and second particles made of metal or semimetal. Examples of quasimetallic materials include gold (Au), platinum (Pt), palladium (Pd), and silicon (Si). Silver (Ag), aluminum (Al), vizmus (Bi), tin (Sn), and zinc (Zn) ) and others. Semimetals are semiconductors as an alternative. The content of the second particle is the total weight of the mixture. Based on the quantity, 8 to 60% by weight, 10 to 50% by weight, 15 to 40% by weight, This is 20 to 30% by weight. The second particle having a content in such a range, For example, the cycle characteristics of the all-solid-state secondary battery 1 will be further improved.

[0054] [Negative electrode layer: Binder] The binder contained in the first negative electrode active material layers 22, 22a, and 22b is, for example, styrene-pigmented styrene. Diene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene Len, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile It can also be polymethyl methacrylate, but it is not necessarily limited to those. In the field of the art in question, if it is used as a binder, then either is possible. Yes, it exists. The binder can also be composed of one or more different binders.

[0055] The first negative electrode active material layer 22 contains a binder, so the first negative electrode active material layers 22, 22a, 22b is stabilized on the negative electrode current collector 21. Also, during the charge-discharge process, the first negative electrode active Despite the volume changes and / or relative positional changes of layers 22, 22a, and 22b, Cracks in the first negative electrode active material layers 22, 22a, and 22b are suppressed. For example, the first negative electrode active material layer If 22, 22a, and 22b do not contain a binder, then the first negative electrode active material layers 22, 22a, and 22 b can be easily separated from the negative electrode current collector 21. Negative electrode current collector 21, 21a, As the first negative electrode active material layers 22, 22a, and 22b detach from 21b, the negative electrode current collector In the portion where 21, 21a, and 21b are exposed, the negative electrode current collectors 21, 21a, and 21b are Contact with the solid electrolyte layers 30, 30a, and 30b increases the likelihood of a short circuit occurring. The first negative electrode active material layers 22, 22a, and 22b are, for example, the first negative electrode active material layers 22, 22a A slurry containing the materials that make up 22b is applied onto the negative electrode current collector 21 and dried. It is manufactured by including the binder in the first negative electrode active material layers 22, 22a, and 22b. During the rally, stable dispersion of the negative electrode active material is possible. For example, by screen printing, When applying the rally onto the negative electrode current collector 21, screen clogging (for example, the negative electrode active material) It is possible to suppress clogging caused by aggregates.

[0056] [Negative electrode layer: Other additives] The first negative electrode active material layers 22, 22a, and 22b are additives used in conventional all-solid-state secondary batteries 1. The agent further includes, for example, fillers, coating agents, dispersants, ion conductivity enhancers, etc. This is possible.

[0057] [Negative electrode layer: first negative electrode active material layer] The thickness of the first negative electrode active material layer 22, 22a, 22b is, for example, 50% of the thickness of the positive electrode active material layer. The following are less than 40%, less than 30%, less than 20%, less than 10%, or less than 5%. The thickness of the highly active material layers 22, 22a, and 22b is, for example, 1 μm to 20 μm, or less than 2 μm. The thickness is 10 μm, or 3 μm to 7 μm. First negative electrode active material layers 22, 22a, 22b If the thickness is excessively thin, the first negative electrode active material layer 22, 22a, 22b and the negative electrode current collector 21, 2 The lithium dendrites formed between 1a and 21b are in the first negative electrode active material layer 22, 22 a,22b are disintegrated, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1. First negative electrode active material If the thickness of layers 22, 22a, and 22b becomes excessively thick, the energy density of the all-solid-state secondary battery 1 The internal resistance of the all-solid-state secondary battery 1 due to the first negative electrode active material layers 22, 22a, and 22b decreases. As the number of components increases, it becomes difficult to improve the cycle characteristics of the all-solid-state secondary battery 1.

[0058] If the thickness of the first negative electrode active material layers 22, 22a, and 22b becomes thinner, for example, the first negative electrode active material The charging capacity of layers 22, 22a, and 22b also decreases. (First negative electrode active material layers 22, 22a, 22b) The charging capacity is, for example, 50% less than the charging capacity of the positive electrode active material layers 12, 12a, and 12b. Below 40%, below 30%, below 20%, below 10%, below 5%, or below 2%. The charging capacity of the first negative electrode active material layers 22, 22a, 22b is, for example, that of the positive electrode active material layer 12, 1 Compared to the charging capacity of 2a and 12b, it is 0.1% to 50%, 0.1% to 40%, and 0.1%. % to 30%, 0.1% to 20%, 0.1% to 10%, 0.1% to 5%, Or it is 0.1% or 2%. The charging capacity of the first negative electrode active material layers 22, 22a, and 22b is If it is too small, the thickness of the first negative electrode active material layers 22, 22a, and 22b will become very thin. In the repeated charge-discharge process, the first negative electrode active material layers 22, 22a, 22b and the negative electrode current collector The lithium dendrites formed between 21 and the first negative electrode active material layers 22, 22a, 22 b is disintegrated, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1. First negative electrode active material layer 22, If the charging capacity of 22a and 22b increases excessively, the energy density of the all-solid-state secondary battery 1 will decrease. As a result, the internal resistance of the all-solid-state secondary battery 1 increases due to the first negative electrode active material layers 22, 22a, and 22b. Furthermore, it is difficult to improve the cycle characteristics of the all-solid-state secondary battery 1.

[0059] The charging capacity of the positive electrode active material layers 12, 12a, and 12b is determined by the charging capacity density (mAh) of the positive electrode active material. The result is obtained by multiplying ( / g) by the mass of the positive electrode active material in the positive electrode active material layers 12, 12a, and 12b. When various types of positive electrode active materials are used, the charging capacity density varies for each positive electrode active material. The mass values ​​are calculated, and the sum of these values ​​represents the charging capacity of the positive electrode active material layers 12, 12a, and 12b. The charging capacity of the first negative electrode active material layers 22, 22a, and 22b is also calculated using the same method. In other words, the charging capacity of the first negative electrode active material layers 22, 22a, and 22b is the charging capacity density of the negative electrode active material. At a rate of (mAh / g), the quality of the negative electrode active material in the first negative electrode active material layers 22, 22a, and 22b It is obtained by multiplying the quantities. When various types of negative electrode active materials are used, each negative electrode active material The charge capacity density × mass value is calculated, and the sum of these values ​​is the first negative electrode active material layer 22, 22a, 22 This is the capacity of b. Here, the charge capacity density of the positive electrode active material and the negative electrode active material is lithium gold This was estimated using an all-solid-state half-cell with the genus used as the relative electrode. This is capacity. By measuring the charging capacity using an all-solid-state half-cell, the positive electrode active material layers 12, 12a, The charging capacity between 12b and the first negative electrode active material layers 22, 22a, and 22b is directly measured. The charge capacity density can be obtained by dividing the calculated charge capacity by the mass of the active material. Then, the positive electrode active material layers 12, 12a, 12b and the first negative electrode active material layers 22, 22a, 22b The charging capacity is also the initial charging capacity measured during the first charge.

[0060] [Negative electrode layer: second negative electrode active material layer] The all-solid-state secondary battery 1, upon charging, for example, the negative electrode current collectors 21, 21a, 21b and the first negative Even if a second negative electrode active material layer is further included, which is positioned between the electrode active material layers 22, 22a, and 22b Good. The second negative electrode active material layer is a plated layer containing lithium or a lithium alloy. It is also a layer. This deposited layer is also deposited by charging the battery. The second negative electrode active The material layer is a metallic layer containing lithium or a lithium alloy. It contains a lithium alloy. Therefore, the second negative electrode active material layer is a metallic layer containing lithium. For example, it acts as a lithium reservoir. The lithium alloy is For example, Li-Al alloy, Li-Sn alloy, Li-In alloy, Li-Ag alloy, Li- These include Au alloys, Li-Zn alloys, Li-Ge alloys, Li-Si alloys, etc. It is not limited to, but refers to any lithium alloy used in the relevant technical field. If any exist, then all are possible. The second negative electrode active material layer is one of such alloys, Alternatively, it can be made of lithium, or of various types of alloys.

[0061] The thickness of the second negative electrode active material layer is not particularly limited, but for example, 1 μm to 1,000 0 μm, 1 μm to 500 μm, 1 μm to 200 μm, 1 μm to 150 μm, The thickness of the second negative electrode active material layer is 1 μm to 100 μm, or 1 μm to 50 μm. If the second negative electrode active material layer is too thin, it will be difficult for it to perform its role as a lithium storage reservoir. If the thickness of the negative electrode active material layer is excessively thick, the mass and volume of the all-solid-state secondary battery 1 will increase, The cycling properties may actually decrease. The second negative electrode active material layer is, for example, It is also a metal foil with a thickness within a certain range.

[0062] In the all-solid-state secondary battery 1, the second negative electrode active material layer is, for example, a combination of all-solid-state secondary battery 1. In the first place, the negative electrode current collectors 21, 21a, 21b and the first negative electrode active material layers 22, 22a, 22b The negative electrode current collector 2 is either placed in between, or after the assembly of the all-solid-state secondary battery 1, it is charged. It precipitates between 1,21a,21b and the first negative electrode active material layer 22,22a,22b. Before assembly of the secondary battery 1, the negative electrode current collectors 21, 21a, 21b and the first negative electrode active material layer 22, When the second negative electrode active material layer 22 is placed between 22a and 22b, the second negative electrode active material layer Since it is a metallic layer containing lithium, it acts as a lithium storage facility. For example, all-solid-state secondary Before assembly of battery 1, negative electrode current collectors 21, 21a, 21b and first negative electrode active material layers 22, 22a A lithium foil is placed between 22b and 22b. This allows the second negative electrode active material layer to be included. The cycle characteristics of the all-solid-state secondary battery 1 are further improved. After assembly of the all-solid-state secondary battery 1, charging When the second negative electrode active material layer is deposited by electricity, during the assembly of the all-solid-state secondary battery 1, the second negative Because it does not contain an active material layer, the energy density of the all-solid-state secondary battery 1 increases. For example, all When charging the solid-state secondary battery 1, the charging capacity of the first negative electrode active material layers 22, 22a, and 22b exceeds the charging capacity. To charge, that is, to overcharge the first negative electrode active material layers 22, 22a, and 22b. Lithium is absorbed into the first negative electrode active material layers 22, 22a, and 22b. The negative electrode active material contained in 2,22a,22b is lithium iodine that has migrated from the positive electrode layer 10. It forms an alloy or compound with the first negative electrode active material layer 22, 22a, 22b. If charging is performed, for example, the back surface of the first negative electrode active material layers 22, 22a, 22b, that is, the negative Lithium Lithium is deposited, and the deposited lithium forms a metal layer corresponding to the second negative electrode active material layer. The second negative electrode active material layer is mainly composed of lithium (i.e., metallic lithium). This is a metal layer. Such results can be seen, for example, in the first negative electrode active material layers 22, 22a, and 22b. The negative electrode active material contained in is composed of a substance that forms an alloy or compound with lithium. This is obtained by the following: During discharge, the first negative electrode active material layers 22, 22a, 22b and the second The lithium in the negative electrode active material layer, i.e., the metal layer, is ionized and moves towards the positive electrode layer 10. Therefore, it is possible to use lithium as the negative electrode active material in the all-solid-state secondary battery 1. Furthermore, the first negative electrode active material layers 22, 22a, and 22b cover the second negative electrode active material layer. Therefore, the second negative electrode active material layer, that is, the protective layer for the metal layer, also serves as a protective layer for lithium It plays a role in suppressing the deposition and growth of ionite. Therefore, short circuits in the all-solid-state secondary battery 1 and This suppresses capacity degradation and, as a result, improves the cycle characteristics of the all-solid-state secondary battery 1. After the assembly of the all-solid-state secondary battery 1, when the second negative electrode active material layer is positioned by charging, The electrode current collectors 21, 21a, 21b and the first negative electrode active material layers 22, 22a, 22b, and the The region between these is, for example, in the initial state or post-discharge state of an all-solid-state secondary battery, lithium This is a lithium-free region that does not contain (Li).

[0063] [Negative electrode layer: negative electrode current collector] The negative electrode current collectors 21, 21a, and 21b do not react with lithium, for example, i.e., they are alloys. The material constituting the negative electrode current collector 21 is composed of a material that does not form either of the above compounds. Examples of materials include copper (Cu), stainless steel, titanium (Ti), iron (Fe), and cobalt. It can also be Co (Co) and nickel (Ni), but it is not necessarily limited to those. However, if it is used as an electrode current collector in the relevant technical field, then all It is possible. The negative electrode current collector 21 is composed of one of the aforementioned metals, or It may also be composed of an alloy or coating material of two or more metals. The negative electrode current collector 21 may be, for example They are either plate-shaped or foil-shaped.

[0064] The all-solid-state secondary battery 1 has, for example, lithium and alloy on the negative electrode current collectors 21, 21a, and 21b. The thin film may further include an element capable of forming a negative electrode current collector 2. It is placed between layers 1, 21a, 21b and the first negative electrode active material layers 22, 22a, 22b. This includes, for example, elements that can form alloys with lithium. Elements that can be used include, for example, gold, silver, zinc, tin, indium, silicon, and aluminum. While it can also be Um, Bizmas, etc., it is not necessarily limited to those, and the relevant technology Any element that can form an alloy with lithium in the field is possible. Yes, the thin film is composed of one of those metals, or of various types of metals. It is composed of an alloy. The thin film is placed on the negative electrode current collectors 21, 21a, and 21b. As a result, for example, a layer is deposited between the thin film and the first negative electrode active material layers 22, 22a, and 22b. The deposition morphology of the second negative electrode active material layer is further flattened, and the cycle characteristics of the all-solid-state secondary battery 1 are improved. It can be improved even further.

[0065] The thickness of the thin film is, for example, 1 nm to 800 nm, 10 nm to 700 nm, 50 The thickness of the thin film is 1 nm to 600 nm, or 100 nm to 500 nm. If the thickness is less than m, the function of the thin film will be difficult to achieve. If the thickness of the thin film is excessively thick... If the thin film itself absorbs lithium, the amount of lithium deposited at the negative electrode decreases, resulting in a solid-state battery. The energy density decreases, and the cycle characteristics of the all-solid-state secondary battery 1 deteriorate. For example, by vacuum deposition, sputtering, plating, etc., the negative electrode current collector 21,2 They may be placed on 1a and 21b, but are not necessarily limited to that method. In the field of this technology, any method capable of forming a thin film is possible. be. [Examples]

[0066] The following examples and comparative examples will further elaborate on this innovative idea. Furthermore, these examples are intended to illustrate the original idea, and by themselves alone, the original The scope of intentional thought is not limited.

[0067] "Example 1: Bi-cell" (Negative electrode layer manufacturing)

[0068] A 10 μm thick Ni foil was prepared as the negative electrode current collector. Additionally, a primary was prepared as the negative electrode active material. Carbon black (CB) with a particle size of about 30 nm, and with an average particle size of about 60 nm Silver (Ag) particles were prepared.

[0069] A mixed powder consisting of carbon black (CB) and silver (Ag) particles in a weight ratio of 3:1. g was placed in a container, and 7% by weight of PVDF binder (Kureha Corporation's #9300) was added to it. A mixed solution was prepared by adding 4g of NMP solution. Next, NMP was added to the mixed solution little by little. The mixture was stirred while adding the other components to produce a slurry. The produced slurry was then placed on Ni foil. Then, apply using a bar coater and leave in air at 80°C for 10 minutes. The laminate was partially dried. The resulting laminate was then vacuum-dried at 40°C for 10 hours. The laminated material is then roll-pressed at a pressure of 300 MPa for 10 ms. The surface of the first negative electrode active material layer of the laminate was planarized. The negative electrode layer was fabricated by the above process. The thickness of the first negative electrode active material layer contained in the negative electrode layer was approximately 7 μm.

[0070] (Positive electrode layer manufacturing) LiNi coated with Li2O-ZrO2(LZO) is used as the positive electrode active material. 0.8 Co 0.15 Mn 0.05 O2(NCM) was prepared. LZO coated positive electrode activity The substance is manufactured by the method disclosed in Korean Public Patent No. 10-2016-0064942. It was manufactured. As a solid electrolyte, the argyrodite-type crystalline material Li6PS5Cl(D50= A 0.5 μm crystalline material was prepared. Polytetrafluoroethylene (PT) was used as the binder. FE) Binder (DuPont's Teplon binder) was prepared. As a conductive agent, carbon nano Fiber (CNF) was prepared. Such materials consist of: positive electrode active material: solid electrolyte: conductive agent: The binder is mixed with xylene solvent in a weight ratio of 84:11.5:3:1.5 to form a mixture. After being formed into a sheet shape, the positive electrode sheet was manufactured by vacuum drying at 40°C for 8 hours. A polypropylene (PP) gasket is placed around the positive electrode sheet. The positive electrode sheet, surrounded by a gasket, is coated with an 18μm thick carbon coating. The positive electrode layer was manufactured by pressing aluminum foil onto both sides of the positive electrode current collector. The thickness of the positive electrode active material layer and gasket contained in the positive electrode layer was approximately 100 μm.

[0071] The positive electrode active material layer is located in the center of the positive electrode current collector, and the gasket surrounds the positive electrode active material layer. It is enclosed and positioned up to the end of the positive electrode current collector. The area of ​​the positive electrode active material layer is equal to the area of ​​the positive electrode current collector. Approximately 90%, and the remaining 10% of the positive electrode current collector area where the positive electrode active material layer is not located. A gasket was placed there.

[0072] (Manufacturing of solid electrolyte layer) Li6PS5Cl solid electrolyte is an argyrodite-type crystalline material (D50 = 3.0 μm, To the crystalline solid electrolyte, add 1.5 parts by weight of acrylic binder to 98.5 parts by weight of solid electrolyte. Then, the mixture was prepared. Octyl acetate was added to the prepared mixture while stirring, and then... Lee was manufactured. The manufactured slurry was applied to the nonwoven fabric using a bar coater, and air The laminate was dried in air at 80°C for 10 minutes. The obtained laminate was then dried at 80°C for 6 minutes. The material was then vacuum-dried. A solid electrolyte layer was manufactured through the above process.

[0073] (Manufacturing of all-solid-state rechargeable batteries) Solid electrolyte layers are placed on both sides of the positive electrode layer, and the first negative electrode is placed on top of these solid electrolyte layers. The laminate was prepared by positioning the negative electrode layers so that the active material layer was in contact with the solid electrolyte layer. The prepared laminate is subjected to plate pressurization at room temperature under a pressure of 500 MPa for 30 minutes. The solid electrolyte layer was sintered by such pressurization, affecting the battery characteristics. This improves the performance. The thickness of the sintered solid electrolyte layer was approximately 45 μm. The density of the Li6PS5Cl solid electrolyte, which is an argyrodite-type crystalline material contained in the decomposed layer, The concentration was 1.6 g / cc. The area of ​​the positive electrode active material layer was approximately 90% of the area of ​​the solid electrolyte layer. The area of ​​the solid electrolyte layer is approximately equal to the area of ​​the positive electrode current collector and the area of ​​the negative electrode current collector, respectively. They were almost identical.

[0074] A pressurized laminate was placed in a pouch, vacuum-sealed, and used to manufacture an all-solid-state secondary battery. (Positive electrode current collection) A portion of the body and the negative electrode current collector protrudes from the sealed outside of the battery, and the positive electrode layer terminals and the negative electrode layer terminals It was used as such.

[0075] "Example 2: Single cell" A positive electrode active material layer and a gasket are placed on one surface of the positive electrode current collector to prepare the positive electrode layer. Except for the fact that the battery was manufactured by sequentially arranging a solid electrolyte layer and a negative electrode layer on one surface of the layer, A solid-state secondary battery was manufactured using the same method as in Example 1.

[0076] "Example 3: Introduction of Sn thin film" A 10 μm thick SUS sheet was prepared as the negative electrode current collector. On this SUS sheet, A tin (Sn) plating layer with a thickness of 500 nm was formed. The all-solid-state secondary battery was fabricated in the same manner as in Example 1, except that a US sheet was used as the negative electrode current collector.

[0077] "Comparative Example 1: Without gasket" The all-solid-state secondary battery was fabricated in the same manner as in Example 1, except that no gasket was used during the production of the positive electrode layer.

[0078] "Comparative Example 2: Without the first negative electrode active material layer" The all-solid-state lithium battery was fabricated in the same manner as in Comparative Example 1, except that the first negative electrode active material layer was not formed and only a Ni negative electrode current collector was used.

[0079] "Comparative Example 3: Ni alone" The all-solid-state lithium battery was fabricated in the same manner as in Comparative Example 1, except that nickel (Ni) particles with an average particle size of 100 nm were used instead of a 3:1 mixture of carbon black (CB) with a primary particle size of about 30 nm and silver (Ag) particles with an average particle diameter of about 60 nm as the negative electrode active material.

[0080] "Comparative Example 4: Graphite alone" The all-solid-state lithium battery was fabricated in the same manner as in Comparative Example 1, except that flake graphite particles with an average particle size of 5 μm were used instead of a 3:1 mixture of carbon black (CB) with a primary particle size of about 30 nm and silver (Ag) particles with an average particle diameter of about 60 nm as the negative electrode active material.

[0081] "Evaluation Example 1: Confirmation of crack generation after fabrication of all-solid-state battery" The cross-sections of the all-solid-state secondary batteries fabricated in Examples 1 to 3 and Comparative Examples 1 to 4 were observed with a scanning electron microscope (SEM) to check whether cracks penetrating the solid electrolyte layer occurred. ​​​​​​​​​​​

[0082] In all-solid-state secondary batteries manufactured in Examples 1 to 3, cracks in the solid electrolyte layer were not observed. On the contrary, in all-solid-state secondary batteries of Comparative Examples 1 to 4, a large number of cracks in the solid electrolyte layer were observed at the corner portions of the positive electrode layer. Therefore, it was confirmed that in the all-solid-state secondary batteries of Examples 1 to 3, the use of the inert member prevents cracks in the solid electrolyte layer during the battery manufacturing process.

[0083] "Evaluation Example 2: Charge-Discharge Test" The charge-discharge characteristics of all-solid-state secondary batteries manufactured in Examples 1 to 3 and Comparative Examples 1 to 4 were evaluated by the following charge-discharge test. The charge-discharge test was carried out by placing the all-solid-state secondary battery in a thermostat at 60°C.

[0084] In the first cycle, charging was carried out at a constant current of 3.6 mA / cm² for 12.5 hours until the battery voltage reached 3.9 V to 4.25 V. Next, discharging was carried out at a constant current of 3.6 mA / cm² for 12.5 hours until the battery voltage reached 2.5 V. 2

[0085] After the second cycle, charging and discharging were carried out 5 cycles under the same conditions as the first cycle.

[0086] In all-solid-state secondary batteries of Examples 1 to 3, charging and discharging proceeded normally until the fifth cycle. In the all-solid-state secondary battery manufactured in Comparative Example 1, a short circuit occurred during the charging process of the second cycle. After the short circuit occurred, charging could not proceed, and the battery voltage did not increase any further. In all-solid-state secondary batteries of Comparative Examples 2 to 4, during the charging process of the first cycle or the first cycle A short circuit occurred during the discharge process.

[0087] In the all-solid-state secondary batteries of Example 1 and Example 2, after the first charging cycle is completed, SEM images were taken of the cross-sections of these batteries to determine the relationship between the first negative electrode active material layer and the negative electrode current collector. In between, a precipitate layer corresponding to the second negative electrode active material layer (i.e., a lithium metal layer) was formed. I confirmed that. In the all-solid-state secondary battery of Example 3, after the first charging cycle is completed, the batteries SEM images of the cross-section were measured, and a second negative electrode active material layer was found between the first negative electrode active material layer and the Sn thin film layer. We confirmed that a precipitate layer corresponding to the highly active material layer (i.e., a lithium metal layer) had been formed. .

[0088] As mentioned above, the all-solid-state secondary battery according to this embodiment is used in various portable devices and vehicles. This can also be applied to the following.

[0089] The above has been a detailed explanation of one exemplary example with reference to the attached drawings, but this invention The original idea is not limited to such examples. In the technological field to which this original idea belongs... If a person is skilled in the art, then within the scope of the technical idea described in the claims, each It is self-evident that variations or modifications of the species can be derived, and these too, It goes without saying that this falls within the technical scope of this original idea. [Explanation of Symbols]

[0090] 1 All-solid-state secondary battery 10 Positive electrode layer 11 Positive electrode current collector 12,12a,12b Positive electrode active material layer 20,20a,20b negative electrode layer 21,21a,21b Negative electrode current collector 22,22a,22b First negative electrode active material layer 30 Solid electrolyte layer 40 Inert member

Claims

1. An all-solid-state secondary battery including a positive electrode layer, a negative electrode layer, and a solid electrolyte layer, the positive electrode layer includes a positive electrode current collector, positive electrode active material layers disposed on both sides of the positive electrode current collector, and a gasket surrounding all sides of the positive electrode active material layers and the positive electrode current collector; the negative electrode layer includes a first negative electrode layer disposed on one surface of the positive electrode layer and a second negative electrode layer disposed on the other surface of the positive electrode layer, each of the first negative electrode layer and the second negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer disposed on one surface of the negative electrode current collector; the solid electrolyte layer includes a first solid electrolyte layer between the positive electrode layer and the first negative electrode layer, and a second solid electrolyte layer between the positive electrode layer and the second negative electrode layer; an area of ​​the positive electrode active material layer is smaller than an area of ​​the solid electrolyte layer in contact with the positive electrode active material layer, an area of ​​the positive electrode active material layer is smaller than an area of ​​the negative electrode current collector.

2. An all-solid-state secondary battery including a positive electrode layer, a negative electrode layer, and a solid electrolyte layer, the positive electrode layer includes a positive electrode current collector, a positive electrode active material layer disposed on one surface of the positive electrode current collector, and a gasket surrounding all side surfaces of the positive electrode active material layer; the negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer, the solid electrolyte layer is disposed between the positive electrode layer and the negative electrode layer; an area of ​​the positive electrode active material layer is smaller than an area of ​​the solid electrolyte layer in contact with the positive electrode active material layer, an area of ​​the positive electrode active material layer is smaller than an area of ​​the negative electrode current collector.

3. An all-solid-state secondary battery as described in claim 1 or 2, wherein the gasket surrounds all sides of the positive electrode active material layer and contacts the solid electrolyte layer.

4. The all-solid-state secondary battery as described in claim 3, wherein the gasket extends to an end portion of the solid electrolyte layer.

5. The all-solid-state secondary battery as described in claim 2, wherein the gasket corrects the area difference between the positive electrode active material layer and the solid electrolyte layer.

6. The all-solid-state secondary battery as described in claim 2, wherein the gasket corrects the area difference between the positive electrode active material layer and the negative electrode current collector.

7. An all-solid-state secondary battery as described in any one of claims 1 to 6, wherein the gasket includes one or more selected from a lithium ion insulator and a lithium ion conductor.

8. An all-solid-state secondary battery described in any one of claims 1 to 6, wherein the gasket includes one or more selected from an insulating polymer, an ion-conducting polymer, an insulating inorganic material, an oxide-based solid electrolyte, and a sulfide-based solid electrolyte.

9. An all-solid-state secondary battery described in any one of claims 1 to 6, wherein the density of the gasket is 10% to 200% of the density of the positive electrode active material contained in the positive electrode active material layer.

10. The all-solid-state secondary battery according to any one of claims 1 to 9, wherein the solid electrolyte layer is a sulfide-based solid electrolyte layer.

11. The sulfide-based solid electrolyte layer is selected from the group consisting of Li 2 S-P 2 S 5 , Li 2 S-P 2 S 5 -LiX (X is a halogen element), Li 2 S-P 2 S 5 -Li 2 O, Li 2 S-P 2 S 5 -Li 2 O-LiI, Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 -LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 S-B 2 S 3 , Li 2 11. The all-solid-state secondary battery according to claim 10, comprising one or more selected from the group consisting of S-P2S5-ZmSn (m and n are positive numbers, and Z is one of Ge, Zn, and Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-LipMOq (p and q are positive numbers from 0 to 10, and M is one of P, Si, Ge, B, Al, and GaIn), Li7-xPS6-xClx (0≦x≦2), Li7-xPS6-xBrx (0≦x≦2), and Li7-xPS6-xIx (0≦x≦2).

12. The all-solid-state secondary battery of claim 10, wherein the sulfide-based solid electrolyte layer comprises an argyrodite-type solid electrolyte containing one or more selected from the group consisting of Li6PS5Cl, Li6PS5Br, and Li6PS5I.

13. The all-solid-state secondary battery of claim 12, wherein the density of the argyrodite-type solid electrolyte is 1.5 to 2.0 g / cc.

14. The positive electrode active material layer further comprises a solid electrolyte, the D50 average particle size of the solid electrolyte contained in the positive electrode active material layer is smaller than the D50 average particle size of the solid electrolyte contained in the solid electrolyte layer, 14. The all-solid-state secondary battery according to claim 1, wherein the D50 average particle size of the solid electrolyte contained in the positive electrode active material layer is 90% or less of the D50 average particle size of the solid electrolyte contained in the solid electrolyte layer.

15. An all-solid-state secondary battery described in any one of claims 1 to 14, wherein the first negative electrode active material layer includes a negative electrode active material and a binder, the negative electrode active material has a particulate form, and the average particle size of the negative electrode active material is 4 μm or less.

16. The all-solid-state secondary battery described in claim 15, wherein the negative electrode active material includes one or more selected from a carbon-based negative electrode active material, and a metal negative electrode active material or a quasi-metallic negative electrode active material, and the carbon-based negative electrode active material includes amorphous carbon.

17. The all-solid-state secondary battery as described in claim 16, wherein the metallic negative electrode active material or semi-metallic negative electrode active material includes one or more selected from gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) and zinc (Zn).

18. The all-solid-state secondary battery described in claim 15, wherein the negative electrode active material comprises a mixture of first particles made of amorphous carbon and second particles made of a metal or semi-metal, and the content of the second particles is 8 to 60 weight % based on the total weight of the mixture.

19. An all-solid-state secondary battery as described in any one of claims 1 to 18, further comprising a second negative electrode active material layer disposed at one or more of between the negative electrode collector and the first negative electrode active material layer and between the solid electrolyte layer and the first negative electrode active material layer, the second negative electrode active material layer being a precipitate layer or a metal layer containing lithium or a lithium alloy.